Ambiência em galpões de criação de frangos de corte na região de Fortaleza – CE - Brasil, Daniel de Freitas (2013)
The Brazilian poultry production has been highlighted among the other areas of the national agribusiness. This enhanced notoriety is the result of research in genetic improvement, nutrition and reproduction, which in recent years are being integrated into studies of ambience and animal welfare. So, the interactions that occur between animals and the different production environments are fundamental factors in order to have better production rates. Therefore, the main objective of this research was to monitor, in real production conditions, two different commercial sheds in their dimensions during the two main seasons in the Northeast (wet and dry), through the constant monitoring of environmental variables (temperature and humidity relative air) and rectal temperature check, beyond a verification of artificial shading techniques for improving the productive environment. The two sheds were monitored since the arrival until exit of the animals, being considered the morning and afternoon as those that generate the greatest comfort and thermal stress, respectively. To obtain a profile of environmental variables over the facilities, mini-stations and data loggers were installed on both sheds, allowing to know the microclimate for which the birds were subjected, as well as viewing of the profile of enthalpy Comfort Index (IEC), which allowed the classification of sheds in accordance with the limits of thermal comfort for broilers from first to sixth week of life. The data of temperature, relative humidity and IEC over the sheds were statistically analyzed and the means compared by Tukey test at 5% of significance. Thus, it was possible to observe that in both seasons, the first two weeks of bird life, the sheds had similar characteristics and along the production chain the different facilities perform distinct influences on animals, and the larger shed the most feasible to the creation of these birds. In addition, it was also found that the use of shading techniques may be a good way to improve the ambience of the sheds causing the locations considered lethal may transform into a suitable microclimatic, reducing the amount of dead birds, increasing productivity and animal welfare, which consequently improves the quality of the final product.